Solid waste management as a response to urban flood risk in Gujrat city, Pakistan - Ijaz, Sana; Muhammad Miandad,; Mehdi, Syed Shajee; Anwar, Muhammad Mushahid; Rahman, Ghani (Penerbit Universiti Kebangsaan Malaysia, 2021)
Solid waste generation is directly proportional to the population; it is also increasing with the global population. Pakistan generates 0.283 to 0.612 kg/capita/day solid waste and per year growth rate is 2.4%. In developing countries the issue of poor solid waste management is prevalent. In Pakistan, 55000 tons solid waste is being generated per day in the urban areas. Only 60% waste is collected and disposed. The remainder is left uncollected which ultimately causes problems of urban flooding, blockage in sewerage system, and outbreak of numerous diseases. The city generates 210 tons solid waste daily, out of which only 165 tons is being collected and disposed. Similarly, the sewerage system covers 60% of the residential area with the pipeline ranging from 9 to 51 inches in diameter. There are two drains which carry waste and rain water out of the city. Current research was conducted to find the relation between poor solid waste management (SWM) and problem of Urban Flooding in Gujrat. The data was collected by measuring level of flood water in major chowks of Gujrat for 10 consecutive rainfalls from 09-04-2018 to 23-09-2018. The flood level data was correlated with the other waste dumping sites in Gujrat and the width of drainage system. While other urban flood prone sites were identified by using GIS (interpolation).The results showed that the areas which have a waste dumping facility face more hurdles after rainfall. Approximately 15-20 inches water accumulates in Jail chowk, Jinnah Road, Circular road, Fawara chowk and Ramtlai chowk even after mild rainfalls, and this level increases during heavy rainfalls. Solid waste generation is continuously on a rise. Along with the rise in economic status of general public, their buying capacity is increasing which is putting pressure on the SWM system. Similarly, as Gujrat’s population growth is 2.2% according to the 2017 census, the number of existing sanitary staff is not enough. There is one sanitary cleaner for 900 people, and as the drainage network of Gujrat is poorly constructed, this number in not justifiable.